Special administrative procedures - Lončar, Zoran (Zbornik radova Pravnog fakulteta u Novom Sadu, 2017)
Despite the quality of legal norms in existing Law on Administrative Procedure, for the realization of citizens’ rights in the Republic of Serbia in accordance to international legal standards, a significant problem are specific administrative procedures. In this type of procedures in recent years have been made many variations from the basic rules of general administrative procedure, which can not be classified as requirements of the specific nature of proceding in certain administrative matters. Therefore it is particularly important that it in new Law on Administrative Procedure (which will begin to fully implement from 1 June 2017) is provided no more only an obligation of compliance of rules in specific administrative procedures with the basic principles of administrative procedure, but now also a prohibition of reducing the level of protection of rights and legal interests of the parties guaranteed by the law on administrative procedure, as well as a legal obligation to harmonize all special procedures with the new law, no later than 1 June 2018. Based on mentioned solutions in the new Law on Administrative Procedures, to citizens of the Republic of Serbia should be allowed to fully realize their rights and legal interests in administrative proceedings, in accordance to the most important international legal standards. However, the drawback of the existing legal solution is a lack of effective mechanism that should ensure that numerous deviations in the special administrative procedures actually remove in prescribed period, and that all special laws harmonize with the new Law on Administrative Procedure. Key words: administrative procedure, a special administrative procedure, general administrative procedure, Law on Administrative Procedure.